Social Inclusion as A Challenge of Multiculturalism in Germany: A Study on Muslim Minorities - Zulkarnain Zulkarnain; Roma Ulinnuha; Raihanah Abdullah (Alfuad: Jurnal Sosial Keagamaan, 2024)
Multiculturalism emphasises cultural and religious diversity in society. It plays an important role in the German context. However, its application in the country still faces challenges that affect the social inclusion of the Muslim minority. Social inclusion is crucial for accepting and integrating minorities into the majority society. Muslim minorities in Germany face several challenges, including discrimination, economic inequality, and limited access to education and employment opportunities. Discrimination is a significant barrier to social inclusion, as stereotypical perceptions and prejudices against their religion and culture often lead to discriminatory experiences in everyday life. Social inclusion is negatively impacted by economic hardship, which limits access to decent employment and equal income. Additionally, limited access to education complicates the integration of Muslim minorities, reducing their chances of achieving economically viable employment and contributing positively to society. Additionally, limited access to education complicates the integration of Muslim minorities, reducing their chances of achieving economically viable employment and contributing positively to society. Additionally, limited access to education complicates the integration of Muslim minorities, reducing their chances of achieving economically viable employment and contributing positively to society. It is important to address inequality in access to education to promote social inclusion. This article explores the factors that affect the social inclusion of Muslim minorities in Germany. Relevant case studies are used to analyze the impact of these factors on the daily lives of Muslim minorities. The article also discusses the efforts that can be made by the government, community organizations, and individuals to improve social inclusion. The aim of this article is to comprehensively address the challenges faced by Muslim minorities in Germany with regards to social inclusion. The goal is to find solutions that promote social justice and equality for all citizens.